A PROCESS-BASED MODEL FOR CHANNEL DEGRADATION: APPLICATION TO EPHEMERAL GULLY EROSION - Casal J.; Lopez J.J.; Giraldez J.V. (My University, 2003)
Ephemeral gullies are important features of soil erosion, yielding large amounts of sediment and dissecting the landscape. In spite of their agricultural and environmental importance, gully erosion is not usually considered in routine schemes for predicting soil loss. An event-oriented process-based model for stream degradation has been adapted for the description of ephemeral gully erosion. The initial channel is considered as prismatic, formed in a uniform soil profile, defined by the watershed swale, and receives upstream and lateral runoff. The resulting gradually varied flow is computed by the standard step method, whereas the erosion, assumed transport-limited, is attributed first to bed erosion, and the remainder is dedicated to the bank erosion. At the end of each time step, channel shape is redefined accordingly with the computed erosion in each reach. A sensitivity analysis revealed that particle density, particle size and roughness coefficient are the key parameters. A calibration of the model simulating the incision of an ephemeral gully in a small watershed with highly erodible soil allowed a proper estimation of soil loss and the gully cross-section shapes along the channel with realistic values of the calibrated parameters.
Keywords: SOIL EROSION; GULLY EROSION; EROSION MODELLING